The relationship between work environment and labour productivity - Suhana Saad; Zaimah Ramli; Novel Lyndon (Penerbit Universiti Kebangsaan Malaysia, 2025)
The oil palm industry is vital to Malaysia's national output, socio-economic development, and employment. Its significant contribution to national income and export earnings highlights the importance of labour productivity in this sector. Recently, however, a decline in Malaysian oil palm production has been attributed to a shortage of labour, especially foreign workers, due to COVID-19 movement restrictions. With Malaysian oil palm, smallholders are now relying solely on local labour, assessing local labour productivity has become crucial. Understanding how local labour productivity is influenced by leadership productivity and work environment is essential. However, there is a lack of research directly exploring the impact of these factors on local labour productivity. This study seeks to address this gap by investigating the relationship between leadership productivity, work environment, and local labour productivity. Data was collected from oil palm smallholders in Sarawak, Malaysia, and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate a strong, positive, and significant relationship between the work environment and local labour productivity. These insights provide practical guidance for oil palm smallholders on strategies to improve local labour productivity.